Adoption Status of Improved Animal Husbandry Practices and its Relationship with the Profile of Dairy Farmers in Kheda District of Gujarat - Divekar, Bharat S; Trivedi, Manoj M (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
This study was conducted to ascertain the extent of adoption of improved dairy husbandry practices and its relationship with the profile of the dairy farmers in the Kheda district of Gujarat. The study was undertaken in four randomly selected talukas of the district, from which 100 dairy farmers were selected randomly. The study revealed that the overall extent of adoption of improved animal husbandry practices in the study area was found to be about 62.78%. The overall highest adoption rate was for reproductive and healthcare management (81.40 and 81.33%) followed by feeding and calf management (77.00 and 62.00%), while the adoption of scientific milking and general management (37.60 and 37.30%) was the lowest. Education, landholding, annual income, and herd size of the dairy farmers had a highly significant (p <0.01) positive relationship. In comparison, social participation and mass media of the dairy farmers had significant (p <0.05) positive relationship with adoption of improved animal husbandry practices. However, family size, experience, and attitude towards dairy farming had a significant negative correlation with the improved animal husbandry practices. The independent variables considered in the present study explained about 38.20% variation (r2 = 0.38) in adoption of the improved dairy husbandry practices.